COVID-19 infection and vaccination status among health care workers in a tertiary care setting in Central Kerala - Bhaskar, Anitha; Akshayakumar, Sobha; Murali, Asha Joan; Alexander, Vipin Sam (International Journal Of Community Medicine And Public Health, 2022)
Background: With the emergence of several new variants of the Severe acute respiratory syndrome- coronavirus disease-2 (SARS-CoV 2) virus, concerns regarding the effectiveness of vaccines arise and the threat of breakthrough infections increase. This study was conducted among health care workers who developed coronavirus disease 2019 (COVID-19) infection to assess their vaccination status and describe their morbidity profile. Methods: A record based descriptive study was conducted among staff of Govt medical College, Kottayam, who became COVID-19 positive between March 2021 and September 2021, using a structured proforma. Data was coded and entered in Excel sheet and analysis was done using IBM Statistical package for social sciences (SPSS) version 20. Results: A total of 444 health care workers at Govt College Kottayam tested positive for COVID-19 during the study period. 369 of the health care workers had taken at least one dose of COVID-19 vaccine, of which 273 (61.4%) were fully vaccinated. As on 31st August 2021, 4917 health care workers have been fully vaccinated, therefore the breakthrough infection rate in the present study was 5.6%. Of those with breakthrough infection 63% were females, 23.1% had history of comorbidities, and 88.6% were symptomatic. The mean interval between receipt of second dose of vaccine and diagnosis was 99 days (range between 16 and 24). Conclusions: Breakthrough infection rate of 5.6% among health care workers presents a major public health challenge in ending the pandemic. Further studies including genomic variant analysis would be more helpful especially with in wake of new variants.